ENHANCING AGRICULTURAL PRODUCTIVITY AND CLIMATE RESILIENCE THROUGH CAPACITY BUILDING: A CASE STUDY OF GIWA AGRO ENTERPRISES’ TRAINING INITIATIVES IN BAUCHI STATE, NIGERIA - Chiwar, I. I.; Musa, A.U.; Balogun, J. A.; Tahir, I. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigates the impact of Giwa Agro Enterprises’ training programs on enhancing agricultural productivity and climate resilience among farmers in Bauchi State, Nigeria. A total of 400 respondents were surveyed, with 91.25% having participated in at least one or more training session, while 8.75% had not. The participants reported a gaining significant knowledge in climate-smart practices, including water conservation (53.95%) and planting drought-resistant crops (33.49%). Following the training, 53.5% of respondents observed moderate improvements in crop yields, with 49% experiencing a 10-20% increase in yield. In terms of confidence, 43.75% of farmers felt confident in managing climate-related challenges, while 49.25% felt moderately prepared to deal with weather extremes like drought and flooding. Despite these positive outcomes, challenges such as financial constraints (19%), lack of resources (14.5%), and insufficient follow-up support (29.75%) were identified as barriers to the full implementation of the practices learned. A regression analysis revealed that factors such as educational level (p<0.01) and farm size (p<0.01) significantly influenced participation in the training. The study concludes that while the training has made a positive impact on agricultural productivity and climate resilience, additional support mechanisms, including financial assistance, resource access, and gender-sensitive approaches, are needed to ensure the sustainable adoption of climate-smart practices among farmers. Enhancing follow-up support, improving infrastructure, and integrating technology to increase the effectiveness of the training programs were recommended.